Macroprudential policy in Malaysia: Implications, key measures and experiences / Sutina Junos...[et al.] - Junos, Sutina; Ma’in, Masturah; Jalil, Siti Ayu (Universiti Teknologi MARA, Kedah, 2019)
Macroprudential policy is a set of measures and institutional that is specifically aimed at containing systemic risks and maintaining financial stability in a country. In Malaysia, the development of the macroprudential policy framework started and gained its momentum after the Asian financial crisis where macroprudential policy instruments are used to manage excesses and imbalances in the financial system and in managing capital flows. The implementation of this policy has been strengthening by Bank Negara Malaysia after Global financial Crisis in order to achieve the objectives of ensuring financial system stability, addressing procyclicality and mitigate the systemic risk. This paper discusses the Malaysia’s experiences in macroprudential policy and the implications in terms of the oversight of macroprudential conditions and the development and application of policy tools